Symptoms to Balloon time Dependent St-Segment Resolution Post Primary Percutaneous Coronary Intervention and its Impact on Mortality - Mohammad Ilyas, Muhammad Nauman Khan, Rizwanullah, Sidra Fayyaz, Khalid Naseeb, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The ST-segment elevation myocardial infarction (STEMI) is an emergency manifestation of coronary artery disease (CAD) that occurs when one epicardial coronary artery is completely blocked. Study aims to test whether symptom-onset-to-balloon time correlates with in-hospital outcomes after primary percutaneous coronary intervention (PPCI) among patients with STEMI. Methodology: under the Hospital Ethical and Research Committee's approval, NICVD's Department of Interventional Cardiology conducted a prospective cohort study that lasted for 6 months. Patients fulfilling the criteria of ST elevation, i.e., ≥ 1 mm in limb leads and ≥ 2 mm in precordial leads, aged > 18 and < 80 years, were included. ST segment elevations and time of symptoms onset were interpreted from the patient's ECG, performed for 30 to 60 minutes. Based on the symptom onset to balloon time, the patients were divided into 2 groups, i.e., < 6 and > 6 hours with follow-up till discharge and 30 days after discharge. An analysis of multivariate logistic regression was conducted to determine if ST-segment resolution and in-hospital mortality were influenced by the time from symptom onset to balloon time. Results: The results showed that Patients with double or triple vessel disease had longer symptom onset to balloon time (p=0.041). Symptom onset to balloon time delayed increased ST-segment resolution by <50% (p=0.000). Symptom onset to balloon time was an important prognosticator of ST-Segment Resolution (< 50% Resolution) but not for mortality. Conclusion: The current study concluded that the association between ST-segment resolution and symptom onset to balloon time shows the significance of symptom onset to balloon time among STEMI patients after PPCI. Keywords: Symptoms to Balloon Time, ST Segment Resolution, Primary percutaneous Coronary Intervention